Consumption Taxes, Income Taxes, and Revenue Sensitivity: States and the Great Recession. (March 2019) - Chernick, Howard; Reimers, Cordelia
This article uses an income-distributional approach to state tax sensitivity to examine the assumption that consumption taxes are more stable than income taxes. We estimate the 2007 to 2009 change in tax revenues as a function of state income distributions and tax burdens by income class. We estimate tax burdens as a function of income tax shares and consumption tax shares. We then simulate the change in tax revenues with tax shares at the national average. If high-income-tax states were to lower their reliance on this tax, the revenue decline during the recession would have been greater . For high consumption tax states, the revenue decline under higher income tax shares would have been smaller . Had they shifted toward consumption taxes, income tax reliant states would not have reduced the cyclical sensitivity of tax revenues during the Great Recession. The interaction between tax burdens and recession shocks by income class is key to these results.